PENGEMBANGAN ALAT PERAGA RESONANSI DAN EFEK DOPPLER BERBASIS SOUNDCARD PC/LAPTOP UNTUK MENINGKATKAN MOTIVASI BELAJAR FISIKA SISWA SMA - Muhammad Caisar Haisy; I Made Astra; Erfan Handoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aims to develop props resonance and Doppler effect soundcard based PC / Laptop to improve students’ motivation to learn physics. This study will be conducted at SMAN 3 Pamulang in June – August 2015. The method used is the Research and Development that development model ADDIE (Analysis, Design, Develop, Implement, and Evaluate). Resonance props made of Pyrex glass and the sound source using the speakers while to display the waveform used software audacity or scope. Props Doppler effect by rail is designed in such a way to show the events of the Doppler effect. Data was collected by means of questionnaries to collect documents from research instruments that have been validated. The final results of this study are expected to props resonance and Doppler Effect-based soundcard pc / laptop can be used to increase the motivation of learners from high school in material sound waves. Keywords: Props resonance, the Doppler effect, Motivation, ADDIE, Audacity / scope.